(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The Research dealt with the role of the target costs in reducing the cost of products in the General Company for soft drinks. One the modern approaches reduce costs and thus increase the ability and continuity to compete in the market. Where the problem of research in identifying the shortcomings in the traditional method used in the company sample research. Which led to a weak control of the cost and the researcher relied on data and costs of the company. The research recommended that the target cost of the company should be applied to the research sample. Training the employees. In addition, preparing training courses for them. He stressed the need to address obstacles that prevent the existence of an effective cost system. Including the application of the target cost method in the research sample company